Efeito da aplicação de calcário sobre os níveis de pH, cálcio, magnésio, fósforo e potássio do solo. - Mário Braga, José; Julião Braga, Luiz; A N Fontes , Luiz (Revista Ceres, 2025)
A study was initiated to examine the relationship between the levels of lime applied and the variation in the pH of the soil and levels of calcium, magnesium, potassium, organic matter and phosphorus. Two experiments were laid out in the same soil (Aluvial textura argilosa), in two locations of the Zona da Mata, Minas Gerais. The experimental design was an incomplete factorialand one of the variables studied was lime which was applied at the levels of 0, 1 500, 3.000, 4.500 and 6.000 kg/ha.